2012
DOI: 10.1111/j.1556-4029.2012.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial Soft Tissue Thickness Database for Craniofacial Reconstruction in Korean Adults

Abstract: One hundred Korean adults (50 men, 50 women) were scanned in the upright position using a cone-beam CT (CBCT) scanner. The soft tissue (ST) thicknesses were measured at 31 landmarks, 10 midline and 21 bilateral landmark sites, and the means and standard deviations were obtained for male and female subjects. While 18 of 31 landmarks showed sex differences, the majority showed higher values for male subjects with the exception of a few landmark sites corresponding to the zygoma area, which showed smaller values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 27 publications
3
87
0
2
Order By: Relevance
“…The thicker STTs in the cheek region in females have been observed in a number of studies [2,5,10,16,19,20,21,28,29,30].…”
Section: Sex Differencesmentioning
confidence: 84%
See 3 more Smart Citations
“…The thicker STTs in the cheek region in females have been observed in a number of studies [2,5,10,16,19,20,21,28,29,30].…”
Section: Sex Differencesmentioning
confidence: 84%
“…In our study, the statistically significant differences are less in number. However, in other studies, no significant bilateral differences have been found [15,16,24,32].…”
Section: Bilateral Differencesmentioning
confidence: 84%
See 2 more Smart Citations
“…head injury or congenital condition) or there may be soft tissue distortion related to the head band, pillow or position of the head in the scanner. Cone Beam CT may resolve some of these issues in future research [103,104] as the radiation dose is low and the patient can sit up during scanning, limiting the effects of gravity of the facial soft tissues.…”
Section: Ethical Issues Relating To Facial Depiction Researchmentioning
confidence: 99%